THE GROWTH OF PIMPINELLA ALPINA HOST CALLUS AT VARIOUS TREATMENTS OF PLANT GROWTH REGULATOR CONCENTRATIONS OF NAA. 2,4 D AND ITS COMBINATION WITH BAP - Fahrauk Faramayuda; Muhammad Irwan; Akhirul Kahfi Syam (Agric, 2022)
Purwaceng (Pimpinella alpina) is an herbal plant that has aphrodisiac, diuretic, and tonic properties. The imbalance between the growth and the exploitation of this plant makes it included in Appendix I (endangered), so its conservation will be crucial. One method of the conservation of this plant is tissue culture. This method is considered one way to induct the callus. The research objective is to find the effect of various treatments of plant growth regulator concentrations of NAA. 2,4 D and its combination with BAP on the growth of purwoceng callus. Concentration of plant growth regulator NAA (0.5 mg L-1, 1 mg L-1, 2 mg L-1), 2,4-D (0.4 mg L-1, 0.8 mg L-1, 1.2 mg L-1 ), a combination of NAA with BAP (0.5 mg L-1 NAA: 1 mg L-1 BAP, 1 mg L-1 NAA: 2 mg L-1 BAP, mg L-1 NAA: 3 mg L-1 BAP) and a combination of 2, 4- D with BAP (1 mg LL 2,4-D : 0.5 mg L BAP, 1 mg L-1 2,4-D : 1 mg L-1 BAP, 2 mg L-1 2,4-D : 1 mg L-1 BAP) into Murashige Skoog medium. Then purwaceng leaf explants were planted on the medium until the growth was seen. This research shows that the plant growth regulator concentration has a different influence on the growth of callus that is recognized by the day of callus induction, colour and callus texture. MS media with growth regulator 1.2 mg L-1 2,4-D can grow callus faster (17 days) with friable texture.